The Benevolent Dictator: Love and Masculine Performativity in Stay with Me - Cruz Gutiérrez, Cristina (Complutense Journal of English Studies, 2023)
This article analyzes the male protagonist of Ayọ̀bámi Adébáyọ̀’s Stay with Me (2017) as an embodiment of the internal contradictions that customary laws and the masculine performativity exert upon Nigerian men. The novel retells Yejide and Akin’s relationship and their struggles to conceive as Akin hides his erectile dysfunction from Yejide and his family. I analyze Akin under Elnathan John’s satiric label of “the benevolent dictator” (2020) exploring how this term engages with the idea of masculinity and male performativity in contemporary Nigeria. For this, I take as a point of departure Patrick K. Uchendu’s study on Nigerian masculinity (2008) and Daniel J. Smith’s notion of “performativity” in Nigerian men (2016). The role of the family in the imposition of customary practices is underlined as essential in Akin progressively becoming a “benevolent dictator”. Akin’s trust in the potential of love and intimacy is measured against the weight of the pressures exerted by the Nigerian family as an institution. In turn, I delve into the role of fear and shame as “prevent[ing] the subject from betraying ‘ideals’” (Ahmed 2014, 106). Ultimately, I claim that the actions of the benevolent dictator in the private sphere echo Adébáyọ̀’s narration of Ibrahim Babangida’s military dictatorship (1985-1993).